2020
DOI: 10.3389/fncel.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone B Facilitates Peripheral Nerve Regeneration by Promoting Autophagy and Migration in Schwann Cells

Abstract: The search for drugs that can facilitate axonal regeneration and elongation following peripheral nerve injury has been an area of increasing interest in recent years. Epothilone B (EpoB) is an FDA-approved antineoplastic agent, which shows the capacity to induce α-tubulin polymerization and to improve the stability of microtubules. Recently, it has been increasingly recognized that EpoB has a regenerative effect in the central nervous system. However, the information currently available regarding the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Many studies have shown that paclitaxel promotes axonal regeneration after central nervous system injury (Hellal et al, 2011;Sengottuvel et al, 2011;Austin et al, 2017). In addition, epothilone B, another microtubule-stabilizing agent, facilitates peripheral nerve regeneration (Zhou et al, 2020). Similar to these earlier studies, the present study illustrates that paclitaxel treatment significantly enhances morphologic and functional recovery in the injured sciatic nerve and its target muscles.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Many studies have shown that paclitaxel promotes axonal regeneration after central nervous system injury (Hellal et al, 2011;Sengottuvel et al, 2011;Austin et al, 2017). In addition, epothilone B, another microtubule-stabilizing agent, facilitates peripheral nerve regeneration (Zhou et al, 2020). Similar to these earlier studies, the present study illustrates that paclitaxel treatment significantly enhances morphologic and functional recovery in the injured sciatic nerve and its target muscles.…”
Section: Discussionsupporting
confidence: 85%
“…While a few studies have investigated the effects of microtubule-stabilizing agents on PNI, the results are contradictory. For example, Hsu et al (2017) reported that paclitaxel impairs nerve regeneration in a rat model of sciatic nerve transection, while Zhou et al (2020) found that epothilone B, another U.S. Food and Drug Administration-approved microtubule-stabilizing agent, facilitates peripheral nerve regeneration. To our knowledge, the current study is the first to describe the role of microtubule dynamics in WD, and the first to explore the effects of both a microtubule-stabilizing agent (paclitaxel) and a microtubuledestabilizing agent (nocodazole) on PNI repair.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effect of fingolimod-releasing fibers on Schwann cell phenotype, we first measured Schwann cell migration distance outward from the whole DRG body. This assessment is important when investigating the regenerative potential of a material for the PNS because the migration of Schwann cells can stimulate greater axon extension (Torigoe et al, 1996;Zhou et al, 2020). Schwann cell migration was significantly greater on all fingolimod-releasing fiber scaffolds compared with the control fibers, with the greatest increase observed on the 0.02% fingolimod-loaded fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive autophagy induced by oxidative stress leads to the death of Schwann cells, whereas docosahexaenoic acid (DHA) attenuates this phenomenon ( Tatsumi et al, 2022 ). In contrast, epothilone B (EpoB) promotes axonal regeneration following peripheral nerve injury by promoting PI3K/Akt signaling-mediated autophagy in Schwann cells and enhancing migration ( Zhou et al, 2020 ). Moreover, autophagy in Schwann cells, which can be activated by nerve growth factor, is crucial for myelin debris clearance to expedite nerve regeneration following peripheral nerve injury ( Li et al, 2020 ).…”
Section: Autophagy In the Innervated Niche Regulates Tumor Progressionmentioning
confidence: 99%